ʺThe role of motivation in the formation of students’ independent learning activitiesʺ - Briukhanova, N.; Hres, L.; Zamchiy, S. (Problems of Engineer-Pedagogical Education, 2024)
The article discusses the importance of motivation in the formation of independent learning activities of students, which leads to the modernization of the educational process. It is proved that the formation of cognitive motivation is an important issue in educational practice, as it determines learning outcomes. Various aspects of motivation that affect the ability of students to learn independently are analyzed. The article presents and analyzes various definitions of the concept of "motivation", considers the most common theories of motivation and learning psychology in the world practice (self-efficacy theory, selfdetermination theory, fixed and growth mindset theory, motivation achievement theory, hierarchy of needs theory), as well as the results of psychological and pedagogical research by Ukrainian scientists. The article characterizes such types of motivation as extrinsic and intrinsic, proves their influence on the independent learning activities of students, as well as the dependence of the influence on the individual characteristics of students. The relationship between universal learning design, which involves the creation of a learning environment that takes into account the diversity of needs and capabilities of students, and the motivation of students' learning activities is shown. The basic principles of universal learning design are characterized. It is noted that the combination of universal learning design and support for motivation of learning activities contributes to improving the quality of learning and achieving better results of students. Examples of independent learning activities of students in higher education institutions are given. It is noted that the implementation of independent learning activities depends on independence in learning, the main aspects and importance of which are described in the article. The article identifies and characterizes various factors that can influence and interact with each other in the process of forming students' independence, as well as change or improve their skills and abilities in this direction. It is established that motivation plays a key role in the formation of independent learning activities of students, as it stimulates activity, the search for knowledge and self-improvement. The relationship between motivation and independent learning activities, ways of influencing each other are determined. The methods used to stimulate the motivation of students and increase their independence in learning (creating an interesting learning environment, stimulating intrinsic motivation, supporting individual needs, creating goals and direction, supporting self-esteem and self-reflection, using positive reinforcement) are characterized.